2012
DOI: 10.1515/cclm-2012-0109
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and oligonutrient status, distribution of amino acids, muscle damage, inflammation, and evaluation of renal function in elite rugby players

Abstract: The conclusions of present study were: 1) the necessity of rugby-specific reference intervals for CK and creatinine parameters; 2) the use of enzymatic creatinine for Modification of Diet in Renal Disease (MDRD) and CKD-EPI, or cystatin C to improve glomerular filtration rate estimation; 3) to take into account the oxidative stress testifying of a bad recovery; and 4) better to take care the nutritional status of the players by adapting needs and amino acids supplementations but also to consider a follow-up of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
0
3
0
2
Order By: Relevance
“…Nonetheless, it was demonstrated that the acute maximal anaerobic exercise, but not the short-term intense anaerobic exercise, raised the plasma Hcy levels [17,18],which can be alleviated by creatine supplementation. While strenuous exercise raised the Hcy plasma levels, the Hcy levels are near normal during the successive pre-season periods in the athletes [19,20]. Enhanced methylation demand might have a role in such elevations of Hcy during prolonged exercise [21].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, it was demonstrated that the acute maximal anaerobic exercise, but not the short-term intense anaerobic exercise, raised the plasma Hcy levels [17,18],which can be alleviated by creatine supplementation. While strenuous exercise raised the Hcy plasma levels, the Hcy levels are near normal during the successive pre-season periods in the athletes [19,20]. Enhanced methylation demand might have a role in such elevations of Hcy during prolonged exercise [21].…”
Section: Introductionmentioning
confidence: 99%
“…We opted to use the MDRD equation because among other equations it yields the strongest correlation with CK activity [15]. Another reason was that the MDRD equation is not sensitive to body mass or body mass index, which have an impact on the result of eGFR [1,9,13,20].…”
Section: Discussionmentioning
confidence: 99%
“…Meyer and Meister [19] described significant changes in creatinine concentrations in a large cohort of professional soccer players and suggested that supplementing of creatine could induce such findings. Another study suggests that anthropometric properties as well as methods of analysis have influenced indices of renal function in rugby players [9]. Basketball players were involved in only one comparative study among other seven sports representatives, which confirmed direct correlation between body mass index and creatinine levels [1].…”
Section: Introductionmentioning
confidence: 87%
“…É conhecido que ferro e zinco consumidos em valores elevados e associados à ingestão insuficiente de micronutrientes com importante propriedade antioxidante, como vitaminas A, E, C, manganês e selênio, podem contribuir para o estabelecimento de ambiente com balanço positivo de radicais livres. Tal combinação contribui para o surgimento de lesões e contusões musculares, infecções relacionadas ao trato respiratório superior, e estabelecimento de maior tempo para recuperação entre sessões de treinamento/competições 7,26,27 . O magnésio, por sua vez, é agente importante com participação em muitas reações ligadas ao metabolismo glicídico, proteico e lipídico.…”
Section: Ingestão De áGua Energia E Macronutrientesunclassified
“…No entanto, não houve diferenças entre Forwards e backs. Lako et al 6 e Gorce-Dupuy, et al 7 também investigaram sob similares intuitos a ingestão alimentar em grupos de jogadores asiáticos e franceses, respectivamente.…”
Section: Introductionunclassified